Story Telling as A Express Feeling Therapy for Patients with Depression: Gambaran Storytelling sebagai Terapi Mengungkapkan Perasaan pada Pasien Depresi - Nurmalasari, Khani; Pratiwi, Arum (Prosiding University Research Colloquium, 2023)
Storytelling is an activity to develop emotions, morals and motivation that creates feelings of joy by providing real examples in the imagination so that someone will more easily absorb and understand the content of the story being told. The aim of this research is to determine the response to storytelling therapy through focus group discussions in depressed patients. This research uses quantitative research with a narrative descriptive approach. The sample for this research consisted of 20 respondents using a non-probability sampling method. Based on the results of research from 20 respondents, it was found that the response to storytelling therapy through focus group discussions was that the majority of patients were able to open up, namely 10 respondents (50%). The conclusion of this research is that all respondents had different responses when given therapy, including being confused, closing themselves off, and being able to open up.